Networking as the basis of flexible dynamic development of universities - Eugenia A. Neretina (Высшее образование в России)
The article deals with networking of universities as one of the modern forms oforganizational changes in the system of higher education. Possible local and cumulative effects gotten by members of the network are revealed. The author analyzes the practice of networking of national universities and the problems on the way to improve the effectiveness of network interaction between universities and their business partners.